ANALYSIS OF PATIENT SATISFACTION WITH EMERGENCY SERVICES AT PRABUMULIH CITY HOSPITAL - Yuliani, Dwi; Harokan, Ali; Asiani, Gema; Sutrisari Nainggolan (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Patient satisfaction is a key metric for evaluating service quality in Emergency Departments (EDs). Service quality is assessed across five dimensions: reliability, responsiveness, assurance, empathy, and tangibility. Objective to analyze the relationship between service quality dimensions and patient satisfaction in the ED of Prabumulih General Hospital in 2025. A cross-sectional quantitative study was conducted with 99 respondents selected via purposive sampling. Data were collected using a structured questionnaire and analyzed using chi-square and logistic regression tests. Significant associations were found between each service quality dimension and patient satisfaction: reliability (p=0.001), responsiveness (p=0.002), assurance (p=0.001), empathy (p=0.001), and tangibility (p=0.001). Logistic regression identified assurance as the most dominant predictor (p=0.000; OR=6.422). The assurance dimension is the strongest predictor of patient satisfaction. Quality improvement efforts in the ED should prioritize enhancing healthcare professionals’ competence and professionalism